2003
DOI: 10.1207/s15327558ijbm1002_01
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the psychosocial and cognitive correlates of physical activity among taiwanese adolescents: A structural equation modeling approach

Abstract: This study examined gender differences in the factors related to physical activity in 832 Taiwanese adolescents. Differences in psychosocial and cognitive correlates were noted by gender group. Taiwanese adolescent girls reported lower physical activity self-efficacy and less perceived benefits and more perceived barriers to being active than boys. Girls compared to boys reported significantly more positive social support, modeling, and norms from parents to be active but significantly less social support and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
74
2
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 20 publications
15
74
2
11
Order By: Relevance
“…Consistent with past studies, there were group differences in self-efficacy based on gender such that males were more confident than females, [27][28] but there were no sex differences in proxy efficacy. The self-efficacy gender difference suggests that after school and parent physical activity promotion programs may need to be structured to raise the confidence of girls.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with past studies, there were group differences in self-efficacy based on gender such that males were more confident than females, [27][28] but there were no sex differences in proxy efficacy. The self-efficacy gender difference suggests that after school and parent physical activity promotion programs may need to be structured to raise the confidence of girls.…”
Section: Discussionsupporting
confidence: 85%
“…Specifically, friend support was found to be the source of support most highly related to physical activity in both lunchtime and after-school settings. Previous studies have demonstrated similar findings on moderate-to-vigorous physical activity during nonschool-time and mean daily physical activity in adolescent girls [11,[35][36][37][38]. Collectively, findings suggest that developing strategies to encourage or assist with friends' physical activity behaviors can be beneficial in promoting physical activity in adolescent girls, regardless of contexts.…”
Section: Discussionsupporting
confidence: 66%
“…Compared with friend support, support from family and teachers for physical activity were found to be less important in both contexts. This finding is understandable because adolescent girls are becoming independent from family and strengthening their identification with peers [11,37]. Interestingly, the effect of family support on physical activity was significant in the after-school context but not at lunch time.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Tal observação não foi surpreendente, pois outros estudos encontraram diferenças de sexo que podem estar afetando o tempo gasto em AF 5 , exigências e preferências 31 , sentimentos e emoções 32 e elaboração de modelo para AF 33 . No entanto, um ponto relacionado a diferenças quanto a influências situacionais entre pessoas do sexo feminino e masculino é que no Irã, enquanto país em desenvolvimento, há diferenças culturais (como opções diferentes para meninas e meninos) que podem estar exercendo impacto na AF entre os sexos.…”
Section: Tabela 4 -unclassified